Pendampingan pengembangan guru SD/MI dalam pembuatan cerita anak menggunakan Artificial Intelligence (AI) - Patimah, Patimah; Mudiyanto, Heru; Jaelani, Aceng (Abdimas Siliwangi, 2025)
Children’s stories play a strategic role in character building, literacy development, and the enhancement of imagination among elementary school students. However, the quality of children’s stories available in society remains relatively low in terms of language use, storyline, and thematic variation. Elementary school teachers have significant potential to become producers of educational children’s stories, yet many face limitations in writing skills and the use of digital technology. This community service program aimed to assist SD/MI teachers in developing children’s stories using Artificial Intelligence (AI). The program employed the Asset Based Community Development (ABCD) approach, consisting of discovery, dream, design, define, and destiny stages. The participants were 10 teachers from SDIT Bilingual Alma Asy-Syauqi Cirebon. Assistance was provided through face-to-face training sessions, online mentoring, and hands-on practice using AI tools for developing story titles, outlines, narratives, and illustrations. The results indicate that the program was successfully implemented in accordance with the ABCD stages and effectively enhanced teachers’ competencies in creating children’s stories. Approximately 70% of participants succeeded in producing complete AI-assisted children’s stories. These findings suggest that integrating AI into teacher mentoring programs is effective in strengthening teachers’ capacity as creators of contextual and educational children’s literature.